Peningkatan Kepuasan Kinerja Karyawan Melalui Penerapan Kepemimpinan Transformasional Dan Komunikasi Interpersonal Pada Bagian Produksi Pt Adis Dimension Footwear Balaraja-Tangerang - Rahmawati, Kareen; Khaeruman, Khaeruman; Abduh, Edi Muhammad (CV. Kalimasada Group, 2024)
Transformational Leadership and good interpersonal communication will be one of the motivating factors for employees to carry out their work optimally. The aim of this research is to determine the increase in job satisfaction through the application of transformational leadership and interpersonal communication in the production section of PT Adis Dimension Footwear Balaraja-Tangerang. Research method What the author uses is an associative quantitative method, where the process of taking samples from a population involves 58 employees. Data were analyzed using SPSS version 26. The results of this research indicate that transformational leadership has a significant effect on increasing job satisfaction. (H1) fever has a significant value of 0.000 < 0.05 and t count > t table (6.322 < 2.004). Interpersonal communication has a significant effect on increasing job satisfaction. (H2) with a significant value of 0.000 < 0.05 and t count > t table (5.590 > 2.004). Simultaneously, transformational leadership and interpersonal communication have an effect on increasing satisfaction. (H3) with a significant value of 0.000 < 0.05 and f count > f table (124,874 > 3.16). Based on the research results, it can be concluded that the variables of transformational leadership and interpersonal communication, either partially or simultaneously, have a significant influence on increasing job satisfaction